2022
DOI: 10.1039/d2gc02429b
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of wine wastes by de novo biosynthesis of resveratrol using a recombinant xylose-consuming industrial Saccharomyces cerevisiae strain

Abstract: A recombinant S. cerevisiae strain was engineered to produce resveratrol from many carbon sources, including xylose, which was used for the synthesis of resveratrol from different wine wastes like vine pruning residue, grape must and wine lees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Alternatively, the use of selected native yeast strains is also a viable alternative; Gaensly et al [ 178 ], isolated beta-glucosidase-producing strains of H. uvarum capable of increasing resveratrol content up to 102% during fermentation of Bordò must ( V. labrusca ) through hydrolysis of piceides. Lately, a study analyzed that the trans- resveratrol concentration in red Tempranillo wines inoculated with T. delbrueckii was three times higher than in wine obtained by using S. cerevisiae and 4.5 times higher when Z. bailii was inoculated [ 179 , 180 ]. Nevertheless, more and more studies increasingly focus on the reuse of wine wastes for bioactive compound recovery, such as resveratrol; in this perspective, Costa et al [ 180 ] showed that the use of an engineered strain of S. cerevisiae , which is also capable of hydrolyzing xylose, on wine waste, such as musts, pruning residues, and wine lees, can lead to modest resveratrol production, representing a viable sustainable alternative in a circular economy context.…”
Section: Enological Yeasts and Health-related Compoundsmentioning
confidence: 99%
“…Alternatively, the use of selected native yeast strains is also a viable alternative; Gaensly et al [ 178 ], isolated beta-glucosidase-producing strains of H. uvarum capable of increasing resveratrol content up to 102% during fermentation of Bordò must ( V. labrusca ) through hydrolysis of piceides. Lately, a study analyzed that the trans- resveratrol concentration in red Tempranillo wines inoculated with T. delbrueckii was three times higher than in wine obtained by using S. cerevisiae and 4.5 times higher when Z. bailii was inoculated [ 179 , 180 ]. Nevertheless, more and more studies increasingly focus on the reuse of wine wastes for bioactive compound recovery, such as resveratrol; in this perspective, Costa et al [ 180 ] showed that the use of an engineered strain of S. cerevisiae , which is also capable of hydrolyzing xylose, on wine waste, such as musts, pruning residues, and wine lees, can lead to modest resveratrol production, representing a viable sustainable alternative in a circular economy context.…”
Section: Enological Yeasts and Health-related Compoundsmentioning
confidence: 99%
“…It is a sustainable development-oriented joint that has developed work within new strategies for the valorization of wine industry waste. Especially focused on the recovery of bioactive compounds, the most relevant article in this cluster exploits a new pathway for resveratrol biosynthesis with a saccharomyces cerevisiae strain, using biomass generated by vine maintenance and wine processing [42]. Furthermore, in that research was estimated through the developed strategy and mass balances that it would be possible to produce approximately 8 kg of resveratrol per hectare of vineyard.…”
Section: Contribution By Authors Countries and Journalsmentioning
confidence: 99%